1998
DOI: 10.1063/1.367006
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of BaTiO3 thin films grown by molecular beam epitaxy

Abstract: Crystallographic and microstructural studies of BaTiO3 thin films grown on SrTiO3 by laser molecular beam epitaxy J. Vac. Sci. Technol. A 15, 275 (1997); 10.1116/1.580524 BaTiO3 thin films grown on SrTiO3 substrates by a molecular-beam-epitaxy method using oxygen radicals Epitaxial ultrathin films of BaTiO 3 were prepared using molecular beam epitaxy. For the substrate, ͑001͒-oriented SrTiO 3 single crystals were used. Controlling the growth conditions of these films as well as the semiconductor thin films,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 16 publications
5
52
4
Order By: Relevance
“…52 In particular, when KNbO 3 or BaTiO 3 thin films are grown on top of a SrTiO 3 substrate, the in-plane polarization of these materials vanishes and the tetragonal c phase is stabilized. 60,61 However, contrary to current thought, in our calculations of the BaTiO 3 /KNbO 3 interfaces, we can observe in Fig. 3 the appearance of a moderate in-plane polarization in these systems along the [110] direction.…”
Section: B In-plane Polarizationcontrasting
confidence: 52%
“…52 In particular, when KNbO 3 or BaTiO 3 thin films are grown on top of a SrTiO 3 substrate, the in-plane polarization of these materials vanishes and the tetragonal c phase is stabilized. 60,61 However, contrary to current thought, in our calculations of the BaTiO 3 /KNbO 3 interfaces, we can observe in Fig. 3 the appearance of a moderate in-plane polarization in these systems along the [110] direction.…”
Section: B In-plane Polarizationcontrasting
confidence: 52%
“…In particular, there have been a lot of calculations and experimental works devoted to epitaxial thin films made of the prototype BaTiO 3 (BTO) ferroelectric . [3][4][5][6][7][8][9] As a result, novel features have been reported in these nanostructures. For instance, FE thin films under short-circuit-like electrical boundary conditions (for which the depolarizing field vanishes or is rather small, as a result of a large screening of the polarization-induced surface charges) exhibit different directions for the spontaneous polarization and different resulting crystallographic phases, depending on the misfit strain arising from the substrate on top of which the film is grown.…”
Section: Introductionmentioning
confidence: 91%
“…While many factors are expected to contribute to these differences, it has been shown that the properties of perovskite thin films are strongly influenced by the magnitude of the epitaxial strain resulting from latticematching the film to the substrate. For example, Yoneda et al [4] used molecular-beam epitaxy (MBE) to grow BaTiO 3 (lattice constant of 4.00Å) on (001)-oriented SrTiO 3 (lattice constant of 3.91Å); they found that the ferroelectric transition temperature exceeds 600 • C, to be compared to the bulk Curie temperature of T C = 130 • C. Other studies have shown that the amount of strain in BaTiO 3 /SrTiO 3 superlattices on SrTiO 3 substrates strongly influences properties including the observed polarization, phase transition temperature, and dielectric constant [5,6,7,8].…”
mentioning
confidence: 99%